Extranodal NK/T‐cell lymphoma, nasal type: Clinical features, outcome, and prognostic factors in 101 cases. (27th July 2018) - Su, Yi‐Jiun; Wang, Po‐Nan; Chang, Hung; Shih, Lee‐Yung; Lin, Tung‐Liang; Kuo, Ming‐Chung; Chuang, Wen‐Yu; Wu, Jin‐Hou; Tang, Tzung‐Chih; Hung, Yu‐Shin; Dunn, Po; Kao, Hsiao‐Wen
Abstract: Objectives: We aimed to define the clinical features, outcome, and prognostic factors for extranodal NK/T‐cell lymphoma (ENKTL) patients in Taiwan. Methods: We retrospectively reviewed 101 ENKTL patients diagnosed between February 1998 and October 2015. Results: The median age of 101 patients was 52 years old (range 22‐85); 76.2% of patients were Ann Arbor stage I/II disease. The 5‐year progression‐free survival (PFS) and overall survival (OS) were 49.9% and 54.8%, respectively. Patients with log[EBV‐DNA] ≥ 3.8 and bone marrow hemophagocytosis at diagnosis had inferior PFS and OS. Most stage I/II patients received combined chemoradiotherapy with anthracycline‐containing regimen, with overall response rate of 96.7%, complete response rate 86.9%, 5‐year PFS 65%, and OS 72%. The relapse rate was 29.3% with a short median disease‐free survival of 6.2 months. In advanced stage patients, overall response rate was only 13.6%, with median PFS 2.3 months, and OS 4.8 months. Age ≥ 60 (HR 3.773, 95% CI 1.733‐8.215, P = 0.001) and stage III/IV (HR 7.785, 95% CI 2.312‐26.213, P = 0.001) were unfavorable prognostic factors for PFS and OS by multivariate analyses. Conclusions: Age ≥ 60 and stage III/IV are independent poor prognostic factors for PFS and OS. Early‐stage ENKTL patients had good response to combined chemoradiotherapy with anthracycline‐containing regimen but with a high relapse rate and short disease‐free survival. Anthracycline‐containing regimen in advanced stage had poor response and dismal outcome.